A reliable GIS-based FAHP-FTOPSIS model to prioritize urban water supply management scenarios: A case study in semi-arid climate. (June 2022) - Noori, Amir; Bonakdari, Hossein; Hassaninia, Maryam; Morovati, Khosro; Khorshidi, Iman; Noori, Ali; Gharabaghi, Bahram
Highlights: Developed a GIS-based-MCDM method to select optimum urban water management scenario. The paper considers triangular fuzzy sets to reduce uncertainty in decision-making. The developed model is robust and flexible to manage required urban water demands. A hydrologic model utilizing WEAP is designed to assess the developed model scenarios. Abstract: The growing problem of urban water shortage and its sustainable management methods is one of today's critical research needs globally. This paper applies an integration of the Geographic Information System (GIS) and Multi-Criteria Decision-Making (MCDM) with the help of triangular fuzzy sets to manage urban water supply priorities in a semi-arid region. Hence, a group decision-making approach was proposed by combining the Fuzzy AHP (FAHP) and the Fuzzy TOPSIS (FTOPSIS) models based on quantitative and qualitative criteria. Therefore, a hierarchical model-based GIS and AHP was developed to classify the effective criteria and determine the Importance Weights (IWs) of criteria according to the experts' opinions and using data layers based on spatial criteria. The priority ranking of scenarios was obtained using the FTOPSIS method. Different criteria such as environmental, geographical, geological, economic, climatic, and social conditions were considered in this study. Furthermore, to assess the water supply scenarios under the essential water demands of the basin cities and suburbs, a hydrologic model utilizing WEAP software was designed. Among the considered criteria, total expense, climatic conditions, and geographic conditions with the IWs values of 0.9, 0.85, and 0.83 were determined as the most effective criteria for evaluating the scenarios' ranking, respectively.